Metachromasia for blood basophils identification in hybrid surubim catfish: Methodological contribution - De Pádua, Santiago Benites [UNESP] (2011)
Different protocols of fixation and hydrolysis of blood smears of hybrid surubim catfish for metachromasia to marking blood basophils were evaluated. For this reason, methanol, acid-alcohol and formalin vapor were tested as fixatives. For hydrolysis of blood smears, HCl, citric acid and 2-Mercaptoethanol + Urea + NaCl solutions was evaluated. After procedures, the blood smears was stained with toluidine blue (0.025%) diluted in McIlvaine buffer (pH 4). The different protocols for fixation and hydrolysis of blood smears for metachromasia influenced the quality of the reaction. Hydrolysis with 2-Mercaptoethanol + Urea + NaCl solutions provided negative results when using methanol and acid-alcohol as fixatives. The fixation with acid-alcohol associated with citric acid hydrolysis provides highest quality reason.